Необходимые и достаточные условия существования "изолированного" решения нелинейной двухточечной краевой задачи - Джумабаев, Д.С.; Темешева, С.М. (Нелінійні коливання, 2012)
Дослiджується нелiнiйна двоточкова крайова задача для систем звичайних диференцiальних рiвнянь при розбиттi iнтервалу та введеннi додаткових параметрiв. Побудовано систему рiвнянь вiдносно параметрiв, що дають можливiсть знайти початкове наближення розв’язку крайової задачi. Встановлено необхiднi та достатнi умови iснування iзольованого розв’язку розглядуваної задачi. By subdividing the interval and introducing additional parameters, we study a nonlinear two-point boundary-value problem for a system of ordinary differential equations. We construct a system of equations with respect to the parameters, which permits to find the initial approximation of the boundary-value problem. We find necessary and sufficient conditions for existence of an isolated solution of the considered problem.